A qualitative analysis of collaborative efforts to build a school-based intervention for multiple common adolescent mental health difficulties in India - Gellatly, Resham; Knudsen, Kendra; Boustani, Maya M.; Michelson, Daniel; Malik, Kanika; Mathur, Sonal; Nair, Pooja; Patel, Vikram; Chorpita, Bruce F. (Frontiers in Psychiatry, 2022)
In low- and middle-income countries (LMICs), the gap between need for mental health (MH) treatment and access to services is stark, particularly among children and adolescents. In service of addressing this treatment gap, the current study provides an in-depth illustration of later-stage collaborative design of a school-based, transdiagnostic MH intervention in New Delhi and Goa, India, using a combination of contextual insights from local stakeholders and knowledge derived from the global evidence base. Using an inductive-deductive approach to qualitative thematic analysis, we examined coded data from qualitative sources related to experiences of developing and implementing an intervention prototype. These sources included notes from meetings attended by treatment development team members and providers, written feedback on protocol materials (e.g., provider manual, student handouts), field notes reflecting researcher observations, and minutes from weekly clinical supervision meetings. Results revealed that codes involving cultural/contextual considerations, protocol material and content, and intervention complexity arose consistently throughout treatment development and across document types, illustrating their central role in finalizing protocol design. These findings have implications for the future of mental health treatment development and implementation globally.